Interannual Variation of Settling Particles Reflects Upper‐Ocean Circulation in the Southern Chukchi Borderland, 2010‐2014. Issue 12 (2nd December 2021) - Onodera, Jonaotaro; Watanabe, Eiji; Itoh, Motoyo; Harada, Naomi; Honda, Makio C.; Tengberg, Anders; Tanaka, Yuichiro; Kikuchi, Takashi
Abstract: Time series monitoring of hydrography and marine settling particles supplies a large amount of information regarding the marine lower‐trophic ecosystem with respect to the changing Arctic Ocean. To investigate the interannual relationship between the settling particles and hydrographic conditions of the western Arctic Ocean, bottom‐tethered sediment trap moorings were deployed at the Northwind Abyssal Plain (NAP) from October 2010 to September 2014 and at the Chukchi Abyssal Plain (CAP) from October 2012 to September 2013 to the east and west of the Chukchi Borderland. The settling particles at both stations contained a significant amount of lithogenic matter, with biogenic particles being a lateral advection of shelf materials from shelf to basin. The many peaks of settling particle fluxes at NAP in 2013–2014 corresponded to the hydrographic events of passing oceanic eddies over the station, in addition to seasonal biological production. The settling particle flux at CAP remarkably increased when Pacific‐origin water advected over the northern shelf of the Chukchi Sea in March–April 2013. Additionally, abundant gelatinous matter was found at NAP and CAP in July–September 2011 and 2014 and in July–August 2013, respectively. The settling flux data of particulate organic matter and the mole ratio and stable isotope ratios of particulate organic carbon and nitrogen reflected the changes in the composition of trapped plankton assemblages under various hydrographic conditions over the course of the four years of the study. Plain Language Summary: In order to monitor changing physical, chemical, and biological characteristics in the Arctic Ocean where sea ice is decreasing, we moored sediment trap, which samples settling particles (also known as marine snow), in the Chukchi Borderland of the Pacific Arctic Ocean from 2010 to 2014. As the monitoring results of settling particles, abundant particles were temporally supplied not only in the summer when biological production was active, but also under seasonal sea ice cover in the winter. Some of the trapped particles were lithogenic matter suggesting their lateral transportation from continental shelf. When oligotrophic water mass in the Canada Basin covered the mooring station, the amount of settling particles decreased significantly. With the hydrographic data and previous studies, it was suggested that advection of oceanic eddies along the oceanic Beaufort Gyre and westward current along the shelf edge of the Chukchi Sea partially contributed to the particle transportation. In addition, mass occurrence of discarded gelatinous house of Appendicularia (Larvacea) was observed in some of the samples obtained in the summer in this study. The temporal mass occurrence of gelatinous matter might partially contribute to the sinking particulate carbon. Key Points: Time series on settling particle fluxes and the particle bulk component in the Pacific Arctic Oceans for 2010–2014 is shown Relationships between settling particles and changes in conditions of sea ice, hydrography, and biological productions are discussed Partial contribution of gelatinous matter to sinking particulate carbon was suspected in some summers during the monitoring period